Role of Inhaled Albuterol in the Management of Transient Tachypnea of Newborn - Hussain, Nayab; Hameed, Muhammad Nadeem; Sobia Naveed,; Riaz, Muhammad Osama; Mamoona Nasr,; Qureshi, Amna Junaid (Indus Journal of Bioscience Research, 2025)
Transient tachypnea of newborns (TTN) is the most common cause of respiratory distress in neonates. Objectives: The objective of this study is to compare the mean TTN score in the inhaled albuterol VS placebo group in addition to standard treatment in patients with Transient tachypnea of newborns. Material and Methods: This randomized control trial (RCT) was conducted in the In-Patient Department of Pediatrics Medicine at Shalamar Hospital, Lahore. Data were collected from 60 patients (30 in each group) by using a random and unbiased selection of participants into treatment and control groups. Results: Albuterol group, 60% of the neonates were male and 40% were female, compared to 55% male and 45% female in the Placebo group. The mean birth weight in the Albuterol group was slightly higher at 3.2 ± 0.3 kg compared to 3.1 ± 0.2 kg in the Placebo group. The mean gestational age was similar between the groups, with 38.5 ± 1.2 weeks in the Albuterol group and 38.4 ± 1.1 weeks in the Placebo group. A higher percentage of neonates in both groups were delivered via C-section, with 65% in the Albuterol group and 60% in the Placebo group. Albuterol group had a significant reduction in TTN score from a baseline of 6.5 ± 0.5 to 2.1 ± 0.4 after 4 hours, while the Placebo group had a smaller reduction from 6.4 ± 0.4 to 4.8 ± 0.6. In terms of tachypnea resolution, 60% of neonates in the Albuterol group recovered within 12 hours, compared to only 20% in the Placebo group. Conclusion: It is concluded that inhaled albuterol is an effective and safe treatment for managing transient tachypnea in the newborn. The use of albuterol significantly reduces respiratory distress and accelerates symptom resolution compared to placebo.